(untitled) (Scientific Researches in Academia, 2023)
The 21st century is known as the era of meaning-focused communicative approach to teaching of grammar. However, most language teachers are found to still follow transmission-based grammar-oriented approaches. It is known that the success or failure of teaching grammar effectively depends on teachers. Therefore, in spite of teaching of grammar being central to language teaching, it is problematic domain for language teachers. That is to say, what teachers do in regard to grammar instruction is an important issue that needs to be investigated. Therefore, through a classroom observation checklist, the present study investigated Nepalese primary-level English language teachers’ practices of teaching grammar. The results revealed that teachers predominantly prefer the traditional focus-on-formS approach, which indicates that even if new way of teaching grammar have been emerged, the teachers are unable to shift their approach of teaching grammar.